2020
DOI: 10.1002/mmce.22146
|View full text |Cite
|
Sign up to set email alerts
|

Compact ultra‐wideband slot antenna with three notched‐band characteristics

Abstract: A very compact ultra‐wideband (UWB) slot antenna with three L‐shaped slots for notched‐band characteristics is presented in this article. The antenna is designed and fabricated using a new stepped slot with different size, integrated in the ground plane, and excited by a 50 Ω microstrip transmission line. The stepped slot is used to minimize the dimensions of the antenna and to achieve an impedance bandwidth between 2.65 and 11.05 GHz with voltage standing wave ratio (VSWR) less than 2. The length of the stepp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…From this study, it can be clearly seen that the proposed design is simple and provides a good performance in terms of compactness compared with previous works. This work is mainly inspired from our previous work cited in [4]. The results obtained in terms of reflection coefficient and radiation pattern have a good agreement with the simulated ones.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…From this study, it can be clearly seen that the proposed design is simple and provides a good performance in terms of compactness compared with previous works. This work is mainly inspired from our previous work cited in [4]. The results obtained in terms of reflection coefficient and radiation pattern have a good agreement with the simulated ones.…”
Section: Introductionmentioning
confidence: 63%
“…The UWB technology was authorized by the federal communication commission to use a new spectrum from 3.1 to 10.6 GHz with effective isotropic radiated power <−41.3 dBm/MHz in commercial applications [3]. The UWB technology is characterized by several advantages, including a wide impedance bandwidth, very-low-power spectral density, considerable channel capacity, and excellent immunity to multi-channel interference [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, analogous to the obtained results in [18][19], the cross-polarized patterns lar ring of about 15.71% and 22.22%. It is revealed that the obtained efficiency surpass the one attained by some recently published papers like in [21]. Additionally, in order to show the importance of the proposed antenna, a comparative review has been established in Table 2.…”
Section: Antenna Geometry and Resultsmentioning
confidence: 96%
“…13 Numerous shapes of patch antenna structures have been listed in the literature survey. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Mostly used designs of UWB antenna are square, circular, triangle, ring, stepped rectangular, elliptical, pentagon, and hexagonal shapes. From that, circular shapes are widely used for UWB systems and it is suitable for antenna miniaturization.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed antenna provides better miniaturization when compared to tapered slot with tuning patch, 21 Combination of Sierpinski Carpet and GiusepePeano Fractals, 22 Parasitic rectangular slot, 23 A broken-heart-shaped patch and slotted partial ground plane, 24 Stepped patch with a ground truncation, 27 Complementary split ring resonator slot and two L-shaped stubs, 28 Half-cutting method, 29 Rectangular slit and an Lshaped stub 30 and slot antenna with three L-shaped slots. 31 In this letter, a novel compact UWB circular antenna for wireless sensor nodes application is proposed and presented. The miniaturization of this low-profile antenna achieved by combination of elliptical ring slot and two crescent-shaped slots in circular patch and two dumbbell-shaped slots in feedline with a partial ground.…”
Section: Introductionmentioning
confidence: 99%